(untitled) (The Review of Diabetic Studies, 2025)
The new agrarian technology has been a powerful influence in determining the extent of tenancy in India. Resumption of self-cultivation by land-owners has been induced by better supply of inputs and other facilities in a number of States. The capitalistic methods have found favour increasingly. In consequence, the area under tenancy, particularly share-crapping, has declined in them. Under pressure small farmers are losing their land to big farmers in different parts of the country and joining the rank of landless labourers. Those States which have experienced increasing migration of both big land-owners and unemployed persons from the rural to the urban areas have found that there has been an increase in absentee land ownership and a concomitant increase in tenancy in their case. The absentee land-owners exploit the actual tillers by indulging in rack-renting, evictions by force and bagger (bonded labour).